RECITATION LEARNING METHOD (RLM): AS ONE OF THE MODERN LEARNING METHODS - Ahmad, Aghniawati; Rahmatika, Nuniek; Khodijah, Siti (Jurnal Ilmiah Didaktika, 2023)
The COVID pandemic that has hit all countries in the world has made the 2013 curriculum a modern learning approach that is appropriate to current conditions. Modern learning places students as learning subjects, and teachers act as facilitators. The research method used in this research is descriptive-qualitative. Aims to determine the implementation of the recitation method in the learning process. Based on the results of the research that has been carried out, it can be seen that the recitation method can be a solution to support learning objectives. The recitation method can stimulate student abilities such as independence, responsibility, and discipline. Therefore, the recitation method is an appropriate learning method that can be carried out by subject teachers in an effort to increase students' learning motivation and train students' independence and responsibility.